2008
DOI: 10.1136/sti.2008.031815
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 2 antibody detection performance in Kisumu, Kenya, using the Herpeselect ELISA, Kalon ELISA, Western blot and inhibition testing

Abstract: Background-In certain parts of Africa, type-specific HSV type-2 ELISAs may have limited specificity. To date, no study has been conducted to validate HerpeSelect and Kalon type-specific HSV-2 ELISAs using both the Western blot (WB) and Recombinant gG ELISA inhibition testing as reference standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 14 publications
2
39
0
Order By: Relevance
“…If HIV-1-infected workers were less likely to participate in the study, this would have led us to underestimate the true HIV-1 prevalence at baseline. Additionally, tests for HSV-2 lack specificity13 when the manufacturer's suggested cut-off is used, and further testing with a western blot ‘gold standard’ could not be performed. To combat this, we repeated our multivariate analysis using a higher cut-off to increase test specificity, and our results were not substantially changed.…”
Section: Discussionmentioning
confidence: 99%
“…If HIV-1-infected workers were less likely to participate in the study, this would have led us to underestimate the true HIV-1 prevalence at baseline. Additionally, tests for HSV-2 lack specificity13 when the manufacturer's suggested cut-off is used, and further testing with a western blot ‘gold standard’ could not be performed. To combat this, we repeated our multivariate analysis using a higher cut-off to increase test specificity, and our results were not substantially changed.…”
Section: Discussionmentioning
confidence: 99%
“…Positively selected amino acid residues were frequently identi- fied in HSV glycoproteins, with the highest number of positively selected sites occurring in gC-1 and gG-2. This finding, along with the detection of five or more positively selected sites in gG-2 and a high number of nonsynonymous substitutions, was an indication that perhaps nucleotide variation and the resulting antigenic variation were impacting the sensitivity or specificity of the Western blot assay in East Africa, where there is a significant difference between ELISA and Western blot results (25)(26)(27)(28). This may be due in part to the U.S. strain of HSV-2 used to provide the antigens in the Western blot and extends to the antigen used in commercial ELISAs.…”
Section: Discussionmentioning
confidence: 99%
“…Because serology tests used to discriminate HSV-1 and HSV-2 infections are frequently inaccurate in East African populations (25)(26)(27)(28), we further examined HSV-2 gG amino acid sequences using phylogenetic methods. The analysis demonstrated that most global strains were dispersed around the tree, with few clusters with bootstrap support greater than 50%; however, there was one large (14 sequences), low-diversity clade (Ͻ0.1%) with moderate bootstrap support (Ͼ60%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, when using the Focus HSV-2 ELISA in a low-risk or heterogeneous setting, the index value for interpreting positivity should be raised from .1.1 to !3.5 (IIa, B), taking into account that this reduces sensitivity for both early and established infection. 29,30,33 Samples with values between 1.1 and 3.5 should undergo confirmation by an alternative method (e.g. Biokit HSV-2 or Kalon ELISA) (IIa, B).…”
Section: Transmission Riskmentioning
confidence: 99%